Outer membrane vesicles derived from Bordetella pertussis are potent adjuvant that drive Th1-biased response - Pschunder, Bernarda; Locati, Lucia; López, Oriana; Martin Aispuro, Pablo; Zurita, Eugenia; Stuible, Matthew; Durocher, Yves; Hozbor, Daniela (Frontiers in Immunology, 2024)
For several years, we have been committed to exploring the potential of Bordetella pertussis-derived outer membrane vesicles (OMV Bp ) as a promising third-generation vaccine against the reemerging pertussis disease. The results of our preclinical trials not only confirm its protective capacity against B. pertussis infection but also set the stage for forthcoming human clinical trials. This study delves into the examination of OMV Bp as an adjuvant. To accomplish this objective, we implemented a two-dose murine schedule to evaluate the specific immune response induced by formulations containing OMV Bp combined with 3 heterologous immunogens: Tetanus toxoid (T), Diphtheria toxoid (D), and the SARS-CoV-2 Spike protein (S). The specific levels of IgG, IgG1, and IgG2a triggered by the different tested formulations were evaluated using ELISA in dose-response assays for OMV Bp and the immunogens at varying levels. These assays demonstrated that OMV Bp exhibits adjuvant properties even at the low concentration employed (1.5 µg of protein per dose). As this effect was notably enhanced at medium (3 µg) and high concentrations (6 µg), we chose the medium concentration to determine the minimum immunogen dose at which the OMV adjuvant properties are significantly evident. These assays demonstrated that OMV Bp exhibits adjuvant properties even at the lowest concentration tested for each immunogen. In the presence of OMV Bp , specific IgG levels detected for the lowest amount of antigen tested increased by 2.5 to 10 fold compared to those found in animals immunized with formulations containing adjuvant-free antigens (p<0.0001).When assessing the adjuvant properties of OMV Bp compared to the widely recognized adjuvant alum, we detected similar levels of specific IgG against D, T and S for both adjuvants. Experiments with OMVs derived from E. coli (OMV E.coli ) reaffirmed that the adjuvant properties of OMVs extend across different bacterial species.Nonetheless, it's crucial to highlight that OMV Bp notably skewed the immune response towards a Th1 profile (p<0.05). These collective findings emphasize the dual role of OMV Bp as both an adjuvant and modulator of the immune response, positioning it favorably for incorporation into combined vaccine formulations.